Water quality and fish habitat assessment of rivers in Johor (Sungai Dengar, Sungai Tui, and Sungai Mengkibol) - Halim, Herni (2009)
Implementation of river rehabilitation programs are due to the apprehension expressed by local community and other stakeholders over the degradation of river and loss of livelihood from fishing and other natural resource-based activities. Usually, river rehabilitation involves works on water quality improvement and landscape enhancement rather than provides essential habitat for aquatic life especially fish. Consequently, this study is carried out in order to reveal the correlation between habitats and fish species towards improving the river rehabilitation efforts. Sungai Dengar near Gunung Belumut, Kluang, Sungai Tui in Bukit Kepong and Sungai Mengkibol in Kluang Town are three rivers that have been chosen for the purpose of the study as the rivers have different landuse and physical conditions. Sungai Dengar which is located in palm oil plantation and recorded as Class II of WQI, exhibits lowers composition of fish species compared to Sungai Tui. However it comprises two species which are not present in the other two rivers; Julong and Bujuk. Nevertheless, Sungai Tui, even though classified under Class III of WQI, exhibits a rich and diverse fish species composition with high economical value species such as Baung akar and Ketutu. Sungai Mengkibol of Class IV is dominated by hardy and tolerant species such as Bandaraya and Tilapia hitam. This study discovers that bankside vegetation, channel units, river size, migratory species and large woody debris are considered as the influential factors in shaping fish species community. The physical characteristics are important as they influence food availability, provide spawning or breeding ground, and protection from predators.